Green Strategy–Based Synthesis of Silver Nanoparticles for Antibacterial Applications - Ssekatawa, Kenneth; Byarugaba, Denis K.; Kato, Charles D.; Wampande, Eddie M.; Ejobi, Francis; Nakavuma, Jesca L.; Maaza, Malik; Sackey, Juliet; Nxumalo, Edward; Kirabira, John Baptist (Frontiers in Nanotechnology, 2021)
Antibiotics have been the nucleus of chemotherapy since their discovery and introduction into the healthcare system in the 1940s. They are used routinely not only to treat bacterial infections but also to prevent infections in patients with compromised immune systems and enhancing growth in livestock. However, resistance to last-resort antibiotics used in the treatment of multidrug-resistant infections has been reported worldwide. Therefore, this study aimed to evaluate green synthesized nanomaterials such as silver nanoparticles (AgNPs) as alternatives to antibiotics. UV Vis Spectroscopy surface plasmon resonance peaks for AgNPs were obtained between 417 to 475 nm. X-ray diffraction analysis generated 4 peaks for both Prunus africana extract (PAE) and Camellia sinensis extract (CSE) biosynthesized AgNPs positioned at 2θ angles of 38.2˚, 44.4˚, 64.5˚, and 77.4˚ corresponding to crystal planes (111), (200), (220) and (311) respectively. Dynamic light scattering analysis registered mean zeta potential of +6.3 mV and +0.9 mV for PAE and CSE biosynthesized nanoparticles respectively. Fourier transform infrared spectroscopy spectra exhibited bands corresponding to different organic functional groups confirming the capping of AgNPs by PAE and CSE phytochemicals. Field emission scanning electron microscopy imaging showed that AgNPs were spherical with average size distribution ranging from 10 to 19 nm. Biosynthesized AgNPs exhibited maximum growth inhibitory zones of 21 mm with minimum inhibitory concentration and minimum bactericidal concentration of 125 µg/ml and 250 µg/ml respectively against carbapenem-resistant bacteria.